Efektivitas konseling kelompok dengan teknik self-management dalam mengurangi prokrastinasi akademik pada siswa - Jultri Sanggalangi; Delia Rambung Pangingi; Apriana Manguma (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2026)
This study evaluates the effectiveness of group counseling integrated with self-management techniques in minimizing students' academic procrastination. Procrastination is a prevalent academic challenge driven by deficiencies in self-regulation, poor time management, and a lack of learning motivation. A quasi-experimental approach was employed, utilizing a pretest-posttest design. The participants consisted of students identified with high levels of task avoidance. The intervention was delivered through structured group counseling sessions focusing on self-monitoring, self-evaluation, and self-reinforcement strategies. The findings reveal a significant reduction in procrastination levels following the treatment. These results reinforce existing theories regarding the critical role of self-regulation in academic behavior. This study implies that organized self-management frameworks within group counseling can effectively foster student discipline and accountability toward their academic obligations.